Studi Bioekologi Parasitoid Tetrastichus brontispae Feer (Hymenopters : Eulophidae) Terhadap Hama Brontispa longissima Gestro (Coleoptera:Chrysomelidae) - Maria Goreti Nere; Yustina Maria Silvia Wonga Puu (Agriculture Faculty of Flores University, 2011)
In recent years, the coconut leaf beetle (Brontispa longissima, Hymenopters: Eulophidae) has been a significant pest in Ende, Indonesia and has destroyed the majority of the coconut crop leading to overall production to decline. In 2007 coconut leaf beetle began being controlled biologically using the parasitoid Tetrastichus brontispae (Hymenopters: Eulophidae). This is now considered locally to be the most effective way to suppress pest populations of coconut leaf beetle but until now there have been no scientific studies on this biological pest control method. This study aims to determine the effectiveness of Tetratichus brontispae parasitoids as a treatment for coconut leaf beetle infestations. This research used a Completely Randomized Design (CRD), which was comprised of three types of experiments. First, the average coconut leaf beetle survival rate was measured when exposed to T. brontispae at five ratios: 1:1, 2:1, 3:1, 4:1, and 5:1. Researchers also measured the effect of Tetratichus brontispae treatment duration using 5treatments, namely: 24 hours, 48 hours, 72 hours, 96 hours, and 120 hours of repeated 10 times. 3) Observation of biological parameters of Tetratichus brontispae was conducted qualitatively. The results showed that treatment with the highest level of parasitization occurred at the ratio of 3:1, as much as 20.75% parasitization, and the lowest level parasitization effect occurred at a level of the 1:1 ratio, as low as 7.07%, with the highest percentage survivability of T. Brontispae occurring on the first day (6.48%) and the lowest on day five at 1.29%. On average, 98.13% of T. Brontispae specimens produced offspring, and an average of 32.71% of specimens gave birth each day. Tetratichus brontispae adults had an average life span of 9-11 days, had no pre- oviposition period with the oviposition period occurring until day five. Specimens would die an average of 6 days following oviposition.